Bone Morphogenetic Protein 4 Alleviates DSS-Induced Ulcerative Colitis Through Activating Intestinal Stem Cell by Target ID3 - Hu, Lei; Xu, Junji; Wang, Xue; Feng, Liang; Zhang, Chunmei; Wang, Jinsong; Wang, Songlin (Frontiers in Cell and Developmental Biology, 2021)
The damage of the intestinal epithelial cells proliferation or intestinal stem cells (ISCs) maintenance may trigger inflammatory bowel disease (IBD), and protecting the ISCs is critical for IBD treatment. Here, we found that in the dextran sulfate sodium (DSS) induced Ulcerative Colitis mice model, colon epithelium and Lgr5+ intestinal stem cells (ISCs) renew quickly during the first 3 days. We also found that during this renewing period, SMAD4 and BMP4 expression were significantly up-regulated. An extra BMP4 treatment could preserve the Lgr5+ ISCs and the colon epithelium turnover, and could significantly decrease colon mucosal damage. Moreover, we found that BMP4 regulated the ID3 expression in the colon epithelium. Depletion of ID3 could significantly reduce the epithelium renewal and ratio of Lgr5+ ISCs at the base of crypts. In conclusion, the present study showed BMP4 could maintain epithelium cellular proliferation and the ISCs function through ID3 in mice with DSS-induced colitis. The administration of exogenous BMP4 supplement could alleviate DSS-induced colitis by restoring epithelium cellular proliferation and ISCs function, suggesting the possible therapeutic function of BMP4 for ulcerative colitis.